A tumour suppressor role for the T-box transcription factor TBX3 in fibroblasts - Cooper, Aretha (Department of Human Biology, 2016)
TBX3, a member of the developmentally important T-box transcription factor family, has been shown to be overexpressed and to behave as an oncogene in several cancers. Much of this work has, however, been performed in carcinomas of epithelial origin and little is known about the role ofTBX3 in sarcomas of mesenchymal origin. This study provides novel evidence to show that TBX3protein, but not mRNA, is upregulated in a number of transformed fibroblast and fibrosarcoma cell lines of mesenchymal origin. Fibro sarcoma is an aggressive soft-tissue sarcoma derived from fibroblasts and, while it occurs very rarely, there are no targeted therapy approaches and survival rates remain low. More work is clearly needed to characterise the molecular mechanisms involved infibrosarcoma development, to allow for more effective treatments to be identified. This study, therefore, aimed firstly to determine the role of TBX3 in transformed fibroblast and fibrosarcoma cells; secondly to investigate the signalling pathways responsible for the upregulation of TBX3; and lastly to identify target genes which mediate the role of TBX3 in these cells. To determine the function of TBX3 in transformed fibroblast and fibro sarcoma cells, cell culture models were generated in which TBX3 was stably knocked down in transformed CT-1 cells, as well as the naturally occurring aggressive HT1080 cell line, and the effect on key features of oncogenesis determined. In both cell lines, a substantial decrease in in vitro cell proliferation, measured using growth curve and BrdU incorporation assays, anchorage independence, measured using soft-agar assays, and migration, measured using scratch and transwell migration assays, was observed. Importantly, the knockdown of TBX3 was also able to significantly increase the in vivo tumour forming ability of HT1080 cells in a mouse model. A TBX3 overexpression cell culture model was also generated in the HT1080 cells and, despite their aggressive nature, increased TBX3 expression resulted in a reduced oncogenic phenotype, including markedly decreased in vivo tumour formation. These results were unexpected and demonstrate for the first time that TBX3 behaves as a tumour suppressor in transformed fibroblast and fibro sarcoma cells, suggesting it may function as either oncoprotein or tumour suppressor depending on cellular context. [Please note: the thesis file has been deferred until June 2018]